2006
DOI: 10.1107/s1600536806008841
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Bis(4-bromophenyl)prop-2-en-1-one

Abstract: Key indicatorsSingle-crystal X-ray study T = 100 K Mean (C-C) = 0.004 Å R factor = 0.038 wR factor = 0.112 Data-to-parameter ratio = 28.3For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
3
8
0
Order By: Relevance
“…The bond lengths and angles in (I) display normal values (Allen et al, 1987) and agree well with those observed in related structures Ng, Shettigar et al, 2006;Patil et al, 2006a,b).…”
Section: Commentsupporting
confidence: 84%
See 1 more Smart Citation
“…The bond lengths and angles in (I) display normal values (Allen et al, 1987) and agree well with those observed in related structures Ng, Shettigar et al, 2006;Patil et al, 2006a,b).…”
Section: Commentsupporting
confidence: 84%
“…Recently, it has been noted that derivatives of chalcones exhibit extremely high and fast non-linearity (Fichou et al, 1988;Kitaoka et al, 1990;Uchida et al, 1998;Goto et al, 1991;Patil et al, 2006a,b;Zhang et al, 1990;Zhao et al, 2000). In view of these features associated with chalcones, we and others have undertaken a number of theoretical and structural studies of such compounds Ng, Shettigar et al, 2006;Patil et al, 2006a,b;Teh et al, 2006;Radha Krishna et al, 2005;Sathiya Moorthi et al, 2005;Uchida et al, 1995), and we report here the structure of the title compound, (I) ( Fig. 1).…”
Section: Commentmentioning
confidence: 78%
“…Bond lengths and angles in (I) display normal values (Allen et al, 1987) and are comparable to those in related structures (Teh et al, 2006;Patil et al, 2006a,b;Ng et al, 2006;Rosli et al, 2006). The least-squares plane through the enone fragment makes dihedral angles of 26.6 (2) and 22.7 (2) with the C1-C6 and C10-C15 benzene rings, respectively.…”
Section: Commentsupporting
confidence: 73%
“…Crystals of the title compound, (I), do not exhibit second-order nonlinear optical properties as they crystallize in a centrosymmetric space group. In view of the interest in the behavior of chalcone and its derivatives, a systematic study of their synthesis and single-crystal structure determinations has been carried out Ng, Shettigar et al, 2006;Patil, Ng et al, 2006;Patil, Teh et al, 2006;Radha Krishna et al, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Santhi & Fun, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Radhika et al, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Selvam et al, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Unnithan et al, 2005;Teh et al, 2006;Uchida et al, 1995). We report here the synthesis and crystal stucture of (I) (Fig.…”
Section: Commentmentioning
confidence: 99%